Exceptional response to lurbinectedin and irinotecan in -mutated platinum-resistant ovarian cancer patient: a case report - Laura Cortesi; Marta Venturelli; Elena Barbieri; Cinzia Baldessari; Camilla Bardasi; Emanuele Coccia; Federica Baglio; Margherita Rimini; Stefano Greco; Martina Napolitano; Stefania Pipitone; Massimo Dominici (Therapeutic Advances in Chronic Disease, 2022)
Lurbinectedin is responsible for DNA recognition and binding, producing double-strand DNA (dsDNA) breaks thus resulting in apoptosis. Sensitivity to lurbinectedin is linked to the nucleotide excision repair (NER) system. Furthermore, irinotecan, a topoisomerase I inhibitor, provokes dsDNA breaks that could be reinforced abrogating the NER system using lurbinectedin. BRCA -mutated patients, already treated with platinum-derived drugs, who suffered DNA damage, cannot repair the breaks due to lurbinectedin interaction, whereas irinotecan provokes a dsDNA break that promotes synthetic lethality. This article describes an exceptional response to lurbinectedin alone followed by the association with irinotecan in a BRCA -mutated platinum-resistant ovarian cancer patient. A 44-year-old BRCA 1-mutated ovarian cancer patient was treated in sixth line with lurbinectedin and irinotecan with a time to further progression (TTFP) equal to 8 months. In our case, the association with irinotecan overcame the resistance to lurbinectedin alone. In conclusion, lurbinectedin and irinotecan demonstrated a promising response in platinum-resistant patients. However, further studies should be conducted to validate our findings and future trials will be important to further define the clinical utility of lurbinectedin.